Guardianship and Marriage Registration in Indonesian Islamic Law: Al-Adillah Al-Shar'iyyah Al Maqāṣidiyyah Perspective - Rohman, Holilur; Malik, Arif Jamaluddin; Candrawati, Siti Dalilah; Annisa , Haifa (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2023)
The renewal of Islamic marriage law in Indonesia is reflected in two essential documents, the Compilation of Islamic Law (the KHI) and the Counter Legal Draft-Compilation of Islamic Law (CLD-KHI). Both documents have distinct legal characteristics. This article examines the marriage guardian's position (wali nikah) and marriage registration in these two legal documents. Utilizing a normative and philosophical approach, this article finds that the marriage guardian is an absolute component of marriage, according to the KHI. In contrast, in the CLD-KHI, the marriage guardian does not apply to women who have reached adulthood and are at least 21. Regarding marriage registration, both documents require its implementation without exception. The difference lies in KHI considering marriage registration as a condition, while CLD-KHI views it as an integral part. Despite having different intentions, the idealized legal objective is the same: to realize Sharia-based benefits. Both are guided by primary sources, hadiths, and the Quran, which generate a spirit of protection and benefit.